Deteksi Serangan ARP Spoofing MITM pada Jaringan IoT menggunakan Metode Random Forest dan Robust PCA - Agung Islamy Aryanto; Yovi Pratama; Afrizal Nehemia Toscany (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
ARP spoofing attacks are a serious threat to network security, particularly in vulnerable Internet of Things (IoT) environments. This final project aims to detect ARP spoofing attacks on IoT net-works using a combination of Random Forest (RF) and Robust PCA methods. RF is chosen for its classification capabilities and handling of non-linear data, while Robust PCA is used for di-mensionality reduction and handling outliers in the data. The dataset used is